Nahdlatul Ulama (NU) dan Kontribusinya dalam Memperjuangkan Kemerdekaan dan Mempertahankan Negara Kesatuan Republik Indonesia (NKRI) - Amin Farih (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Religious mission of Nahdlatul Ulama (NU) in consolidating power against Dutch colonialism is a part of the struggle of NU for defending religious ideology and nationalism, as a form of patriotism (ḥubbu al-waṭan). NU had to expel the Dutch colonialists because it is religious teaching. The law had already become a decision of the religious leaders (kyai) of NU, which ultimately rise "the resolution of jihad". This resolution became a powerful principle of student-army who are combined both in of Ḥizbullāh and Sabīlillāh. Some views of NU that the principles of equality, justice, removing all forms of exploitation and colonization, are the spirit NU to maintain consistency of state sovereignty, strengthen the nation integrity. Applying historical method, this study described the role and contribution of NU in fighting against Dutch colonialism, for independence and defend the nation's sovereignty within the framework of the unitary state of Indonesia (NKRI).